Field Measurement Test on Protection Ratio For DVB-T2 Interfered By TV White Space Devices - Lessy Sutiyono Aji (Syntax Literate, 2022)
TV white space (TVWS) refers to the unused UHF and VHF spectrum owned by primary users, such as TV (DVB-T2) broadcasters in a certain location. The protection of primary users' interference from white space devices has been the major implementation issue. Protection ratio setting is commonly used to limit the amount of transmission power that white space devices can permit. In the present study, the simulation and experiment for the proposed protection ratio values are compared. Simulation using Monte Carlo has been conducted. Field measurements were implemented to see whether the protection ratio value could be used to assist the government in implementing TVWS. The outcomes showed that the simulation-based protection ratio was 1 dB greater than the field test result. The results indicate that the simulation model can be used as a reference for the government to estimate the value of the protection ratio and facilitate better efficient implementation